Concentração letal LC50 do extrato aquoso de folhas de terminalia catappa em guaru, phalloceros caudimaculatus - Claudiano, Gustavo da Silva [UNESP] (2012)
This trial was conducted in order to determine the 50% lethal concentration (LC (I) 50-96h) of the aqueous extract of dried leaves of Terminalia catappa, a plant with antifungal, antibacterial and antiparasitic activity. Due to the increasing use of herbal medicines in aquaculture, its use is an option for controlling diseases in fish. Toxicity tests are important before recommending any treatment, since some products have therapeutic concentration close to lethal. To conduct the study used 135 fish species Guarus (Phalloceros caudimaculatus), exposed to increasing concentrations of: 0.0, 50.0, 100.0, 150.0, 200.0, 250.0, 300.0 mL of stock solution per liter of water. The results were calculated by the method Trimmed Spearman Karbo, demonstrating that the 50% lethal concentration (LC (I) 50-96h) estimated was 208.52 mL / L, with lower limit of 187.79 mL / L and higher 231.54 mL / L. Observed changes in behavior of the test organisms at concentrations above 250 mL / L decrease in the levels of dissolved oxygen and pH. Concentrations below 250 mL /L result in mortality rate near zero, so the aqueous extract shown low toxicity.